Faces of Joblessness in Lithuania A People-centred perspective on employment barriers and policies - Pacifico, Daniele (OECD Social, Employment and Migration Working Papers, 2018)
In the aftermath of the financial and economic crisis, large shares of working-age individuals in Lithuania either do not work or only to a limited extent. By 2013, several years after the start of the labour-market recovery, 21% were still without employment during the entire year, and a further 11% had weak labour-market attachment, working only a fraction of the year, or on restricted working hours. This paper applies a novel method for measuring and visualising employment barriers of individuals with no or weak labour-market attachment, using household micro-data. It first develops indicators to quantify employment obstacles under three broad headings: (i) work-related capabilities, (ii) incentives, and (iii) employment opportunities. It then uses these indicators in conjunction with a statistical clustering approach to identify unobserved ("latent") groups of individuals facing similar combinations of barriers. The resulting typology of labour-market difficulties provides insights on the most pressing policy priorities in supporting different groups into employment. A detailed policy discussion illustrates how these empirical results can inform people-centred assessments of existing labour-market integration measures and of key challenges across different policy areas and institutions. The most common employment obstacles in Lithuania were health limitations, limited work experience, and scarce job opportunities. Although financial disincentives and care responsibilities were less widespread overall, they remained important barriers for some groups. A notable finding is that just over one third of jobless or low-intensity workers face three or more simultaneous barriers, highlighting the limits of narrow policy approaches that focus on subsets of these employment obstacles in isolation